Broke and patriotic : why poor Americans love their country - Duina, Francesco G., 1969- (Stanford, California : Stanford University Press, 2018)
In Broke and Patriotic, Francesco Duina contends that the best way to answer these questions is to speak directly to America's most impoverished. Spending time in bus stations, Laundromats, senior citizen centers, homeless shelters, public libraries, and fast food restaurants, Duina conducted over sixty revealing interviews in which his participants explain how they view themselves and their country. He masterfully weaves their words into three narratives. First, America's poor still see their country as the "last hope" for themselves and the world: America offers its people a sense of dignity, closeness to God, and answers to most of humanity's problems. Second, America is still the "land of milk and honey:" a very rich and generous country where those who work hard can succeed. Third, America is the freest country on earth where self-determination is still possible.
A people's country -- Broke and patriotic -- Heading to Alabama and Montana -- The last hope -- The land of milk and honey -- Freedom -- Reconciling poverty and patriotism -- An unshakeable bond.
Includes bibliographical references (p[ages 215-223) and index.
Keywords: Patriotism -- United States; Poor -- United States -- Attitudes; Patriotismo -- Estados Unidos; Pobres -- Estados Unidos -- Actitudes